Markets and marketing : - Preston, Lee E (Scott, Foresman, 1970)
The book provides the character and role of marketing activity in the economy and in the firm. It attemps to provide a framework for collecting and sorting out these random experiences and observations, and a basis for systematically gathering new ones, so that significant elements can be identified and analyzed and inferences and implications brought out.